Critical success factors in franchise business: A cross analysis among Muslim and non Muslim franchisors in Malaysia - Md Isa, Filzah; Othman, Siti Norezam; Hoe, Chee Hee; Hussin, Zolkafli; Mohd Harif, Mohd Amy Azhar; Mohd Jani, Mohd Yusop (Society for Business Research Promotion, 2012)
Franchising is one of a means to embark in business by entrepreneurs, specifically Muslim entrepreneurs.The objective of this research is to identify the critical success factors of Muslim franchisors in conducting their franchise business in Malaysia.The cross case study approach was used to analyse the data.Six Muslim franchisors and seven Non Muslim franchisors were selected as the sample cases.There were two important variables which had been identified as very critical to the success of local franchise business namely marketing orientation factors and entrepreneurial based factors. The Muslim franchisors highlighted competition as their main business market orientation.They also demonstrated high entrepreneurial based factors in the product dominant sector.For the service dominant sector, Muslim franchisors stressed more on customer and inter functional coordination.However, they scored moderate achievement motivation and low risk taking as well as innovation.The implication of this study was the barriers and promoters on development of Muslim franchisors were identified and further action was to be taken to develop successful Muslim franchisors.